(untitled) (Hoboken, N.J., 2005)
Featuring numerous case histories illustrating how each innovation was developed and how the principles supporting each were put into practice, Management Innovation in U.S. Public Water and Wastewater Systems: Establishes standards for measuring success as utilities innovate and improve; Evaluates financial concerns and innovations; Illuminates innovations in planning for future investments; Explores tools for customer communications and other technology concerns; Details state-of-the-art management strategies, including Six Sigma.
Keywords: Water utilities,Municipal water supply,Sewage disposal; Management,Management,Management; United States,United States,United States